2023
DOI: 10.1590/1980-5373-mr-2023-0060
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Molecular Weight of Pullulan Produced by Aureobasidium pullulans from Industrial Waste

Victor R. L. Oliveira,
Victória V. Coelho,
Eliana F. C. Sérvulo
et al.

Abstract: The objective of this research was the sustainable development of pullulan and its structural and rheological characterization. In addition, the cultivation of the A. pullulans Y2092 strain by submerged fermentation on a laboratory scale was evaluated, valuing the use of industrial waste (residual brewery's yeast), RBY, and a low-cost renewable raw material VHP (very high polarization sugar). A 2 2 factorial statistical design of experiments was used to analyze the molecular weight of the pullulans produced. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Figure 4b,c also show a similar trend regarding the saponified films, but the peak intensity varied depending on the PVAc/PULL ratio, which might be due to the change in material property. However, when FT-IR spectra of the unsaponified films were considered, Figure 4c shows a very precise broad peak in the range of 3000-3600 cm −1 , as PULL also contains the -OH group [28]; it was also revealed that PVA was obtained from PVAc in the presence of PULL.…”
Section: Ft-ir Spectroscopymentioning
confidence: 99%
“…Figure 4b,c also show a similar trend regarding the saponified films, but the peak intensity varied depending on the PVAc/PULL ratio, which might be due to the change in material property. However, when FT-IR spectra of the unsaponified films were considered, Figure 4c shows a very precise broad peak in the range of 3000-3600 cm −1 , as PULL also contains the -OH group [28]; it was also revealed that PVA was obtained from PVAc in the presence of PULL.…”
Section: Ft-ir Spectroscopymentioning
confidence: 99%
“…The dynamic viscosity of the polymer's solution with different concentrations-2, 4, 6, 8, 10, and 12% w/v-was performed using a rotational Ametek Brookfield DVPlus viscometer with a ULA spindle, at different shear rates, ranging from 0.1 to 500 s −1 at 25 • C [23]. The viscosimetric analyses of the samples were performed at 25 • C.…”
Section: Measurement Of Dynamic Viscositymentioning
confidence: 99%